Pengaruh Pembelajaran PAI Berbasis Gamifikasi Terhadap Belajar Siswa - Mayasri Nasution (PT Anugerah Literasi Indomedia, 2025)
This study aims to examine the influence of gamification-based Islamic Religious Education (IRE) learning on students’ learning outcomes. Islamic Religious Education learning still faces challenges related to low student motivation, interest, and engagement due to the dominance of conventional teaching methods. Using a library research approach, this study analyzes various relevant scholarly sources to explore the concept, characteristics, and impacts of gamification in IRE learning. The findings indicate that gamification-based IRE learning has a positive effect on students’ motivation and learning interest, and contributes to the improvement of learning outcomes in cognitive, affective, and psychomotor domains. Gamification also encourages active student participation and supports the internalization of Islamic values in a more contextual and meaningful way. However, the effectiveness of gamification largely depends on instructional design and the role of teachers in guiding the learning process to remain aligned with the objectives of Islamic education. Therefore, gamification-based IRE learning can be considered an innovative and relevant alternative learning strategy. Penelitian ini bertujuan untuk mengkaji pengaruh pembelajaran Pendidikan Agama Islam (PAI) berbasis gamifikasi terhadap belajar siswa. Pembelajaran PAI selama ini masih menghadapi tantangan rendahnya motivasi, minat, dan keterlibatan siswa akibat penggunaan metode konvensional yang kurang variatif. Melalui pendekatan kajian literatur (library research), penelitian ini menganalisis berbagai sumber ilmiah yang relevan untuk mengkaji konsep, karakteristik, serta dampak penerapan gamifikasi dalam pembelajaran PAI. Hasil kajian menunjukkan bahwa pembelajaran PAI berbasis gamifikasi berpengaruh positif terhadap motivasi dan minat belajar siswa, serta mampu meningkatkan hasil belajar pada aspek kognitif, afektif, dan psikomotorik. Gamifikasi juga mendorong keterlibatan aktif siswa dan membantu internalisasi nilai-nilai Islam secara lebih kontekstual dan bermakna. Namun demikian, efektivitas gamifikasi sangat bergantung pada desain pembelajaran dan peran guru dalam mengarahkan proses belajar agar tetap selaras dengan tujuan pendidikan Islam. Oleh karena itu, pembelajaran PAI berbasis gamifikasi dapat dijadikan sebagai strategi pembelajaran alternatif yang inovatif dan relevan.